Dimensi Tafsir Sufistik-Falsafi Guru Sekumpul Dalam Risālah Wasīlah - Syarif Hidayatullah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2023)
This article delves into the sufistic-philosophical interpretations put forth by Guru Sekumpul, a prominent figure in 20th-century Kalimantan, primarily through his work, Risālah Wasīlah. Employing a historical-philosophical approach, the paper dissects the manifold concepts embedded within the text as follows: First, Guru Sekumpul’s interpretations have a significant connection with the prominent figures and concepts of philosophical sufism. Consequently, Guru Sekumpul’s sufism should not only be confined to the realm of ishārī-akhlaqī-’amalī, but should also be acknowledged as a product of naẓarī-falsafī thought. Second, the positioning of Risālah Wasīlah and Guru Sekumpul’s teachings within the historical framework of Sufism in South Kalimantan signifies an attempt to unify the philosophical sufism that predates ishārī sufism. Third, the polemic surrounding philosophical sufism in Kalimantan is recognized as a specific and temporally limited phenomenon that should not lead to the exclusion of philosophical sufism from the broader discourse. This perspective is particularly significant when considering the pivotal role and historical dominance of philosophical sufism in the 16th century. Fourth, the teachings of philosophical sufism should transcend mere cosmological theory and extend to encompass a deep spiritual engagement aimed at reaching the core of religious experience. This approach advocates for an essentialist, universal, and moderate foundation for religious practices, in order to mitigate the risks of rigid, superficial (suḥṭīyah), excessive (tashaddud), and extreme (ifrāṭ).